Concepts of Occupational Protection, Occupational Safety and Health and Well-Being of Employees at Work - Tsopa, Vitaly; Cheberyachko, Serhii; Sharovatova, Olena; Deryugin, Oleg; Lapko, Kyrylo (Social Development and Security, 2025)
Purpose: analysis of concepts of labor protection, occupational safety and health at work and well-being of employees at work in order to find further ways of developing organizational management systems. Мethod: comparative analysis of various existing concepts of labor protection and benchmarking with elements of brainstorming. Research results: аn analysis of three existing concepts was conducted and their strengths were identified, which allow reducing the number of injuries, increasing labor productivity and creating conditions for the comprehensive development of the employee. The basic components of each concept on labor protection, safety and health of employees at work and well-being of employees at work were established.The advantages of each concept were determined. It was shown that the concept of well-being of employees at work allows creating a psychologically positive and supportive working environment. Theoretical implications: consists in identifying the components of well-being at work that go beyond physical safety and include holistic care for the mental, social, and financial health of employees, indicating the future vector of employee personality development. Practical implications : consists in identifying the strengths and weaknesses of existing concepts of occupational safety and health and safety of workers at work, which became the basis for identifying key ideas for developing the concept of well-being of workers at work.